Strategi Pemasaran Efektif untuk Meningkatkan Daya Saing dan Pertumbuhan Bisnis UMKM di Era Digital Modern - Stella Hanako Sayyidinaa; Yholanda Azzahra; Hamdani, Hamdani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Marketing strategy is something that includes the entire system related to the aim of planning a price, distributing and promoting purchasing needs. This research aims to find out what strategies can be used to market a business or product for MSMEs. The research method used is descriptive analysis with a qualitative approach, including literature studies on marketing strategies for MSME businesses. The result of this study is a utilization strategy in marketing a business or product is to take advantage of digital technology which as we know has a lot of roles for our lives. In addition, providing attractive promos and providing a time limit if or the number of items so that consumers feel they have to quickly and immediately buy the products we sell. In conclusion, an effective marketing strategy for MSME businesses combines the use of digital technology, the development of a strong brand identity, strategic collaboration, a deep understanding of consumers, and then in a creative marketing approach.